2014
DOI: 10.1097/ta.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

A 26-year comparative review of United Kingdom helicopter emergency medical services crashes and serious incidents

Abstract: Accidents and serious incidents relating to HEMS operations in the United Kingdom have been comprehensively identified for the first time, allowing an estimation of overall accident and fatal accident rates and comparison with other countries' HEMS operations. Data collection and analysis were hampered by obscurity of data sources and poor availability of data. In a time of increasing HEMS use in the United Kingdom, it is essential to be mindful of safety, and standardization of data collection will improve fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
1
18
1
1
Order By: Relevance
“…During late autumn and winter, our region has only 8 h of daylight and frequent storms and snow with low visibility. Helicopter flights at night and in low visibility are associated with a higher level of risk, and helicopter pilots follow stricter flight rules 7. Our proportion of canceled helicopter flights caused by bad weather are only slightly more than half of what Lawless et al reported, probably because of different helicopters, pilot experience, and local weather conditions 11.…”
Section: Discussionmentioning
confidence: 55%
“…During late autumn and winter, our region has only 8 h of daylight and frequent storms and snow with low visibility. Helicopter flights at night and in low visibility are associated with a higher level of risk, and helicopter pilots follow stricter flight rules 7. Our proportion of canceled helicopter flights caused by bad weather are only slightly more than half of what Lawless et al reported, probably because of different helicopters, pilot experience, and local weather conditions 11.…”
Section: Discussionmentioning
confidence: 55%
“…In this data-set, there has been a reduction of fatal accidents per million flight hours from the period 1982-1987 (level of fatal accidents: from 41 to 47) to the period 1987-2004 (level of fatal accidents: from 9.1 to 18). Based on our review we have seen a reduction of accidents in the later periods, and that there is a need for more standardized reporting of helicopter accidents to be able to compare results and learn from different countries, in line with the findings from [16].…”
Section: Accident Levelsmentioning
confidence: 56%
“…A full analysis of unwanted incidents and successful recoveries based on more instrumentation, such as video recordings, would have given a deeper understanding of incidents, but no such data have been identified. In general incident and accident data are of poor quality and should be improved, as mentioned by [16]. Continuous data transmission of "black box" data to the outside is also absent at present.…”
mentioning
confidence: 99%
“…The authors have previously defined the composition, estimated activity and rate of crashes and serious incidents in the UK HEMS fleet, and compared it to published data from other countries 1. It is estimated that approximately 230 000 HEMS missions occurred in the UK between 1987 and 2013, with 13 accidents or serious incidents.…”
Section: Introductionmentioning
confidence: 99%